A multi-criteria decision support method towards selecting feasible and sustainable housing renovation strategies. (1st January 2021) - Serrano-Jiménez, Antonio; Femenías, Paula; Thuvander, Liane; Barrios-Padura, Ángela
Abstract: This research presents a decision support method for housing managers to identify the most appropriate renovation strategy, which combines a multi-criteria assessment of ten renovation factors together with an economic feasibility analysis. In contrast to the majority of decision support systems, this method not only assesses the impact of the renovation proposals, but also includes and evaluates the management of the renovation process through a procedure of quantifying and weighting multiple social, technical, and economic variables related to the renovation work. The method, based on two representative cases of housing renovation projects in Sweden, has been designed and tested and is also applicable to other locations, multi-family buildings, and ownership models. Via a graphical display, the results show the impact generated during the work, the benefits obtained after the interventions, and the economic feasibility in different timeframes of each design strategy, which supports housing owners' decision-making and promotes feasible and suitable actions from a multidisciplinary approach. The conclusions highlight the possibility of implementing renovation strategies at various levels and provide policy implications of this method for a cleaner operation in the building sector with responsible management of urban regeneration by generating sustainable renovation rates and satisfactory proposals. Highlights: Decision support method for housing renovation to select appropriate strategies. Multi-criteria assessment and feasibility study related to the renovation process. Iterative design and testing of the method based on two reference cases from Sweden. Display of impacts, benefits and profitability of different action proposals. Practical perspectives and policy implications to achieve cleaner renovation rates.